Plant-Extract-Mediated Synthesis of Metal Nanoparticles - Yunhui Bao; Jian He; Ke Song; Jie Guo; Xianwu Zhou; Shima Liu (Journal of Chemistry)
Metal nanoparticles (MNPs) have been widely used in several fields including catalysis, bioengineering, photoelectricity, antibacterial, anticancer, and medical imaging due to their unique physical and chemical properties. In the traditional synthesis method of MNPs, toxic chemicals are generally used as reducing agents and stabilizing agents, which is fussy to operate and extremely environment unfriendly. Based on this, the development of an environment-friendly synthesis method of MNPs has recently attracted great attention. The use of plant extracts as reductants and stabilizers to synthesize MNPs has the advantages of low cost, environmental friendliness, sustainability, and ease of operation. Besides, the as-synthesized MNPs are nontoxic, more stable, and more uniform in size than the counterparts prepared by the traditional method. Thus, green preparation methods have become a research hotspot in the field of MNPs synthesis. In this review, recent advances in green synthesis of MNPs using plant extracts as reductants and stabilizers have been systematically summarized. In addition, the insights into the potential applications and future development for MNPs prepared by using plant extracts have been provided.